Fair and foul [ beyond the myths and paradoxes of sport - Eitzen, D. Stanley (Rowman & Littlefield, 2009)
"Americans have long cherished sport for its display of superb skills, heroic efforts, selfless teamwork, uncanny strategies, exuberance, spontaneity, and loyalty. This book moves beyond the myths and media hype to take a closer look at America's love of sport and how it so often comes in conflict with our most basic values. With reverence yet a sharp eye for the influence of big business, corruption, price gouging, political maneuvering, and media grandstanding, Eitzen portrays famous and lesser known events from professional and college sports, including well known coaches and players, to give us a deeper understanding of what sports means to us and how it affects our everyday world."--Publisher's description